PENERAPAN INKUIRI TERBIMBING DIPADU NUMBERED HEAD TOGETHER BERBASIS LESSON STUDY UNTUK MENINGKATKAN HASIL BELAJAR SISWA - Intan Rezki Kurniasari; Herawati Susilo; Utami Sri Hastuti (Jurnal Pendidikan: Teori, Penelitian, dan Pengembangan, 2016)
The purpose of this research is to describe the implementation of the guided inquiry combined with the numbered head together which is based on lesson study to improve learning outcome. The type of this study is Classroom Action Research (CAR) based on lesson study. The result of the research indicated that the implementation of the guided inquiry combined with the numbered head together which is based on lesson study considerably can improve learning outcome domain cognitive from the cycle I to the cycle II increase of 26,67%, from the cycle II to the cycle III increase of 20%, but also can improve learning outcome domain psycomotor from the cycle I to the cycle II increase of 13,4% and from cycle II to the cycle III increase of 10%.Penelitian ini bertujuan untuk mendeskripsikan penerapan inkuiri terbimbing dipadu numbered head together berbasis lesson study untuk meningkatkan hasil belajar. Jenis penelitian ini adalah PTK berbasis lesson study. Hasil penelitian menunjukkan, penerapan inkuiri terbimbing dipadu numbered head together berbasis lesson study dapat meningkatkan hasil belajar ranah kognitif dari siklus I ke siklus II sekitar 26,67%, siklus II ke siklus III meningkat sebesar 20% dan meningkatkan ranah psikomotor dari siklus I ke siklus II sekitar 13,4% %, siklus II ke siklus III meningkat sekitar 10%.